Pelatihan Pembelajaran Terintegrasi Augmented Reality Menggunakan Assemblr Edu di SMAN 1 Leuwiliang - Acep Musliman; Chandra S. Haratua; Atu Solihah; Intan Afrianti; Kinanti Fadillah Kusuma; Martahan Bostanglaut Togatorop; Nia Rahmasari (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This community service activity was conducted as an effort to introduce integrated learning innovations based on Augmented Reality (AR) technology using the Assemblr Edu application to teachers at SMAN 1 Leuwiliang, Bogor, and several other schools in Bogor Regency. This activity was motivated by the underutilization of interactive digital technology in the learning process, particularly in helping teachers visualize abstract material. The implementation methods included preparation, webinar promotion, webinar implementation, a brief technical training session on creating learning materials using the Assemblr Edu application, and guidance in designing AR-based learning content during the webinar. Participants were asked to create AR-based teaching materials using Assemblr Edu according to the subjects they teach. In addition to providing theoretical material, the implementation team also conducted hands-on practice to ensure participants developed the skills to create AR content independently. The results of the activity showed high enthusiasm from the participating teachers, with 85% of participants stating that the training was very helpful and that they felt more confident in integrating AR technology into classroom learning. Participants were also able to produce several prototypes of Augmented Reality-based learning media that can be used as interactive teaching tools. This activity not only improved teachers' technological literacy but also broadened their understanding of how digital technologies such as AR can be creative solutions to enhance the quality of learning and student engagement. Through this community service activity, it is hoped that teachers will become agents of change in utilizing innovative technologies to create more engaging, interactive, and technology-driven learning experiences that align with the demands of 21st-century educational technology. Additionally, this program serves as a strategic step to strengthen teachers' capacity in addressing future challenges in digital learning.